Anti-MDA5 positive dermatomyositis complicated with rapidly progressive interstitial lung disease – a case report. Issue 6 (2nd November 2018) - De Backer, Eva; Gremonprez, Félix; Brusselle, Guy; Depuydt, Pieter; Van Dorpe, Jo; Van Haverbeke, Carole; Goeminne, Pieter C; Derom, Eric
Abstract: Case presentation : We present a case of a 55-year-old Caucasian male with manifestations of dermatomyositis complicated with rapidly progressive interstitial lung disease (RP-ILD). Diagnosis of anti-MDA5 positive dermatomyositis was made. Discussion : Myositis specific antibodies (MSA) can be used for diagnosis and predicting prognosis in patients with polymyositis and dermatomyositis. Anti-MDA5 positive dermatomyositis should be considered in patients presenting with dermatomyositis and a disease course resembling antisynthetase syndrome in the absence of antisynthetase autoantibodies, especially if a remarkably high ferritin is noted. Anti-MDA5 autoantibodies have been associated with RP-ILD and adverse outcome. In patients with anti-MDA5 autoantibodies, early diagnosis and aggressive immunosuppressive treatment may improve prognosis. Conclusion : This case highlights the importance of determining MSA in patients with dermatomyositis and associated interstitial lung disease, as this has implications for diagnosis, prognosis and therapy.